On the Provenance of a Kunstkammer Elephant - Anastasia Fedotova (Prohistoria)
The museum of the Zoological Institute of the Russian Academy of Sciences in St. Petersburg exhibits a taxidermy piece and a skeleton of an Asian elephant (Elephas maximus Linnaeus, 1758), mounted in 1806-1807 for St. Petersburg Kunstkammer. The anatomical accuracy and the technique of this taxidermy piece are exceptional for the beginning of the nineteenth century yet the name of its creator has not been known. A careful study of archival documents survived in the Archives of the Academy of Sciences permitted us to reconstruct the identity of scientists and artists involved in the making: it was a prop artist and papier-mâché craftsman Сarl Thimpont (died 1829), while anatomist Piotr Zaslavsky (1764-1846) supervised the construction of the skeleton. Likely, they both consulted the drawings made by anatomist Petrus Camper in 1802. The elephant was a diplomatic gift from the emir of Bukhara to Catharine II. The animal arrived to St Petersburg by autumn of 1796, was kept in the menagerie of the Imperial Hunting Yard, and died in the April of 1806.